Total Protein and Total Fucose in Sera of Patients with Thyroid Dysfunction and Control - Rajah, T. M.A (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Total protein and total fucose were determined in sera of thyroiddisorder patients.Sera of (40) diagnosed by consultant hyperthyroidism, and 40 hypothyroidism  were analyzed  for  the above  parameter  for  control, sera of (40) normal individuals were used.They   were   healthy   with    no  appearing   disorder   results   analysis revealed  no significant  differences  (P